The intercalation of bicyclic and tricyclic carboxylates into layered double hydroxides - Khan, A; Williams, G; Hu, G; Rees, N; O'Hare, D (2010)
Twenty-four nanocomposites built from layered double hydroxides and bicyclic and tricyclic carboxylates have been synthesised for the first time. Eight carboxylates were successfully intercalated into [LiAl2(OH) 6]Cl·yH2O, [Ca2Al(OH) 6]NO3·yH2O, and [Mg2Al(OH) 6]NO3·yH2O, and the products fully characterised. Guest species incorporated include 1-adamantane carboxylate (1-AC) and 5-norbornene-2-endo-3-exo-dicarboxylate. In some cases, carbonate anions were co-intercalated with the organic guest, and in others poorly crystalline aluminium hydroxides formed as by-products. Sharper resonances were observed in the 13C solid-state NMR spectra of the 1-AC intercalates than in the spectrum of pure 1-AC, suggesting increased order in the arrangement of the cyclic cages in the intercalates. Where possible, time-resolved in situ X-ray diffraction was employed to study the nanoscopic steps involved in the intercalation reactions. These investigations showed that the reactions are one-step processes, proceeding directly to the fully exchanged intercalate with no intermediate phases. The intercalation processes were found to be nucleation controlled. © 2010 ElsevierInc. All rights reserved.